2021
DOI: 10.1177/0363546521997116
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Injuries and Their Association With Previous Concussion History: A Prospective Study of High School Volleyball and Soccer Players

Abstract: Background: Sports-related concussions may have a neurobiological recovery period that exceeds the period of clinical recovery, and one consequence of an extended neurobiological recovery may be the risk of subsequent musculoskeletal injuries. Most literature citing an increased risk of musculoskeletal injury after a sports-related concussion has been reported in populations other than adolescent athletes. Purpose/Hypothesis: The purpose was to prospectively determine if incidence rates of musculoskeletal inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…Investigation of previous sport-related injury or concussion as a potential injury risk factor has been previously outlined in various studies and a systematic review regarding youth sports, specifically. [23][24][25] Studies considering the health of athletes at the time of their return to play after shoulder injury could serve to prevent some potential injury cases. This study serves to describe current shoulder-related injury trends in Canadian youth ice hockey.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of previous sport-related injury or concussion as a potential injury risk factor has been previously outlined in various studies and a systematic review regarding youth sports, specifically. [23][24][25] Studies considering the health of athletes at the time of their return to play after shoulder injury could serve to prevent some potential injury cases. This study serves to describe current shoulder-related injury trends in Canadian youth ice hockey.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of access to complete medical records typically makes survey acquisition of self-reported HxC and self-ratings of various aspects of physical, emotional, and sleep-related well-being the only feasible means to document the existence of potential contributors to elevated injury risk. Several previous studies have confirmed an association between HxC and subsequent musculoskeletal injury among adolescent athletes ( 22 , 25 , 42 , 43 ), but only one study has been focused on the identification of perceptual–motor deficiencies that may elevate their injury susceptibility ( 23 ). Thus, the purpose of this prospective cohort study was to identify factors derived from survey responses and a VR test of perceptual–motor performance and possible interactions between factors that most strongly predict the subsequent occurrence of a core or lower extremity injury (CLEI) among male and female high school athletes.…”
Section: Introductionmentioning
confidence: 99%
“…With an estimated global incidence of 600 cases per 100 000 people annually,1 concussions present a significant financial burden on those seeking appropriate healthcare 2. Emerging evidence has recognised an elevated risk of lower extremity musculoskeletal injury (LEMI) following concussion in high school,3 4 collegiate5–7 and professional athletes8 after sport resumption, with 1.6 times higher LEMI incidence in athletes with a concussion history than in their non-concussed counterparts 9. While the underlying mechanism for the elevated LEMI risk remains uncertain, previous research has suggested the full recovery of neuromuscular control following concussion10–12 may extend beyond the clinically defined recovery period 10 13.…”
Section: Introductionmentioning
confidence: 99%